Management of rheumatic fever and rheumatic heart disease in children and adolescents presently (Research, Society and Development, 2022)
Objective: This study has the purpose of analyzing how rheumatic fever and rheumatic heart disease in children and adolescents are managed in the modern era. Methods: It is an integrative review, executed from bibliographic research on the PubMed, Web of Science and Biblioteca Virtual em Saúde platforms. The descriptors were searched on the MeSH (Medical Subject Headings) platform, being them: “Rheumatic fever”, “Heart disease”, “Child” e “Adolescent”. Relevant articles were selected to promote current and pertinent analysis and discussions. Results and Discussion: Rheumatic fever and rheumatic heart disease have their prevalence associated to socioeconomic issues, being evident the relation between an educative coefficient and the reality analyzed. Besides, it is crucial the promotion of early diagnosis as well as the dissemination of prophylactic measures to be implemented in regions where people suffer from the most serious ways with those diseases. Conclusion: The pathologies studied are still a public health issue. However, identifying the risk factors and enabling early diagnosis and treatment make it possible to mitigate the impact of those illnesses. It is also perceived that education about health issues was an effective way of promoting a healthy life in the observed populations.